Big data in healthcare - the promises, challenges and opportunities from a research perspective: A case study with a model database - Adibuzzaman, Mohammad; DeLaurentis, Poching; Hill, Jennifer; Benneyworth, Brian D (AMIA ... Annual Symposium proceedings, 2017)
Recent advances in data collection during routine health care in the form of Electronic Health Records (EHR), medical device data (e.g., infusion pump informatics, physiological monitoring data, and insurance claims data, among others, as well as biological and experimental data, have created tremendous opportunities for biological discoveries for clinical application. However, even with all the advancement in technologies and their promises for discoveries, very few research findings have been translated to clinical knowledge, or more importantly, to clinical practice. In this paper, we identify and present the initial work addressing the relevant challenges in three broad categories: data, accessibility, and translation. These issues are discussed in the context of a widely used detailed database from an intensive care unit, Medical Information Mart for Intensive Care (MIMIC III) database.